Nests and seasonal cycle of Neocorynura pubescens in Colombia (Hymenoptera: Halictidae) - Michener, Charles D. (Revista de Biología Tropical, 1977)
In the Dept. de Antioquia, Colombia, Neocorynura pubescens is active throughout the year. Females collect pollen from weedy Compositae. Many nests in the banks of a small ditch were surprisingly similar in number of inhabitants, structure, manner of construction, and re-use to those of the strikingly different looking species, N. fumipennis, in Costa Rica. Mating presumably occurs in the nesting area; a clump of males prepared to pass the night on a perch in that area.